On a set avoiding solutions of the Erd\H{o}s-Straus equation : Erd\H{o}s-Straus equation - Agama, Theophilus (My University, 2022)
We apply the notion of the olloid to show that a certain set contains no solution of the Erd ̋os-Straus equation
Keywords: olloid; Erdos; Straus; equation